SP5.1.7 What did we miss? A 5 - year retrospective cohort study calculating the endoscopy miss rate for UGI cancers in a Scottish district general hospital. (28th October 2021) - Rashid, M; Clyde, D; Driscoll, P J; Jafferbhoy, H
Abstract: Aims: Despite the widespread use of endoscopy, upper gastrointestinal (UGI) cancers still present at an advanced stage. As survival is closely linked to stage and time of diagnosis, failure to detect subtle precancerous changes at endoscopy may compound poor prognoses. This study calculates the miss rate of UGI cancer over a 5-year period at a district general hospital. Methods: All patients diagnosed with UGI cancer between January 2015 - December 2019 were identified from a prospectively collected cancer registry. Electronic health records and Unisoft GI reporting tool were used to identify patient demographics and previous UGI endoscopies. 'Missed cancers' were defined as patients who had a normal endoscopy within 3 years of their cancer diagnosis. Results: The median age at diagnosis was 72.2 years (age range 24 - 98, n = 408) with a male predominance of 2:1 (66.6% male vs 33.4% female) in keeping with UK statistics. Within this 5 year study period, there were 22 missed cancers (5.4%, n = 408). A year by year break down shows miss rate in 2015 of 3% ( 3, n=100), 2016 of 4.2% (5, n=120), 2017 5.5% (5, n=91), 2018 6.4% (6, n=94) and most recently in 2019 3.2% (3, n=94). Conclusions: In 2014, a meta-analysis by S.Menon et al recorded a miss rate of 11.3%. More recently published UK studies report miss rates between 6% - 7.3%, more in keeping with our local rate of 5.4%. Further assessment is required to assess whether the 2017 BSG and AUGIS UGI endoscopy quality standard statement will improve this rate.